Population structure of the wild boar (Sus scrofa) in two Mediterranean habitats in the western Iberian Peninsula (FOLIA ZOOLOGICA, 2003)
Wild boar population structure was studied in two well-preserved forests of western Iberian Peninsula, one located in a typically Mediterranean zone (vegetation mainly holm oak Quercus ilex and various tall-shrubs species), and the other in a more Atlantic area (mainly oak Q. pyrenica but with abundant cork oak Q. suber in some places). Data were colleted during hunts in monterias' area between the 1994/95 and 2000/2001 hunting seasons (October to February). 972 hunted wild boars were sexed and aged in the field, using growth patterns and tooth attrition. The mean age of hunted wild boars differed in the two zones. 2.11 years old in holm oak forest, and 1.78 years old in oak forest. This difference may result from shurb cover density and its effect on hunting dog, efficiency in rooting out wild boar. However, mean age was similar other zones of Europe. Proportionately more females were taken than males demonstrate the usefulness of Mediterranean hunting in contributing to management and conservation.